The Determinant Factors of E-Commerce Usage Behavior During Flash Sale Program - Arta Moro Sundjaja; Gladys Valentina Arisanto; Sarah Fatimah (CommIT (Communication and Information Technology) Journal, 2020)
The research objective is to analyze the determinant factors of the purchase intention during a flash sale program. It is conducted from October 2018 to January 2019. The researchers apply a quantitative approach. The sampling technique is snowball sampling. The survey data are collected from 210 respondents who shop online in Indonesia using questionnaires. The data are examined using Structural Equation Modelling (SEM) with AMOS ver. 25. The research results indicate that the effect of perceived usefulness, information quality, and web quality on purchase intention are mediated by attitude. The flash sale program has a moderating impact on purchase intention. The effect of perceived ease of use and trust in the purchase intention mediated by attitude is not significant. The R-squared value of attitude on e-commerce is 0.527, and purchase intention is 0.369. These research results are important for e-commerce management to understand the essential factors of purchase intention during a flash sale program.